PERSONNEL MANAGEMENT DEVELOPMENT ISSUES IN MULTINATIONAL CORPORATIONS OF THE WORLD ECONOMY - Оlena Zharikova; Kateryna Cherkesenko (Izdevnieciba "Baltija Publishing", 2021)
Today the modern world is on the verge of a redistribution of transnational corporations, which compete with each other for new spheres of influence, markets of production and outlet, technology and maximum possible profits. Globalization and internationalization of production and capital, privatization, the creation of world political and economic associations, and the liberalization of trade have placed them at the center of modern economic development. The article reveals the issues of personnel management development in transnational corporations of the world economy. On the basis of the research theoretically and practically grounded theoretical and methodological approach to the organization of activities of transnational corporations in the globalization processes of the economy. The practical significance of ways and forms of organization of activities of transnational corporations in ensuring the development of international production, sales, trade and financial complex with a single decision-making center in the host country with its branches, representative offices and subsidiaries is analyzed. Research shows that transnational corporations have an important function in the development of the modern world economy. They directly affect the economies of recipient countries, accelerate the internationalization of economic life, as well as the scientific and technological process. Attracting foreign direct investment gives a country access to the financial resources of TNCs, as well as facilitates its integration into global economic processes and access to foreign markets. Transnational capital has created a new system of international relations, which has led to the formation of supranational institutions of governance. In addition, TNCs are actively influencing the processes of globalization. This article discusses the risks associated with the personnel of TNCs and the ways of economic and social protection of employees. In recent years, the international labour market has used the social package as a form of remuneration for work, which should be broadly understood as the employer's provision of material benefits in the form of fringe benefits, compensation, privileges and social guarantees. The social package can be implemented with the help of existing legislative mechanisms, such as contractual regulation of collective labour relations, normative regulation of labour in local legal acts of business entities, the written form of the employment contract.